The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1021/jp055603h
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Protein-Conjugated Silver Sulfide Nanorods in the Bovine Serum Albumin Solution

Abstract: Highly ordered silver sulfide nanorods conjugated with the Bovine Serum Albumin (BSA) protein have been successfully achieved at ambient temperature. Such a process is very simple and controllable, directly using silver nitrate and thioacetamide (TAA) as the reactants in the aqueous solution of BSA. The products have been characterized by XRD, HRTEM-SAED, SEM-EDS, TG-DTA, FT-IR, and CD spectroscopy. The results of the research show that the as-prepared Ag2S nanorods are monodispersed with sizes about 40 nm in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
101
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 36 publications
2
101
0
Order By: Relevance
“…The mixed product obtained in this way is unstable since it would require additional reactant for stable fixation. However, this instability provides some advantages after the submucosal injection, allowing a gradual release of silver nitrate in the surrounding tissue [13,14]. This phenomenon maintains the silver nitrate in the tissue for a longer time, favouring a stronger and permanent local effect.…”
Section: Discussionmentioning
confidence: 99%
“…The mixed product obtained in this way is unstable since it would require additional reactant for stable fixation. However, this instability provides some advantages after the submucosal injection, allowing a gradual release of silver nitrate in the surrounding tissue [13,14]. This phenomenon maintains the silver nitrate in the tissue for a longer time, favouring a stronger and permanent local effect.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 The unique optical and electronic properties of gold nanoparticles make them ideal candidates for cell targeting and also as efficient tools for bioassays. 25 On this basis, we sought to develop a fluorescence-based biosensor using liver cancer cell surface-specific (LCCS) antibody-conjugated gold colloids to probe cancer cells specifically in a mixed cell population.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the bioconjugation of nanoparticles have been reported in the recent years [28][29][30][31][32]. Jose-Yacaman and co-workers reported the synthesis of gold nanoparticles directly conjugated to BSA by chemical reduction in aqueous solution [29].…”
Section: Introductionmentioning
confidence: 99%
“…Jose-Yacaman and co-workers reported the synthesis of gold nanoparticles directly conjugated to BSA by chemical reduction in aqueous solution [29]. In another study, highly ordered silver sulfide nanorods conjugated with BSA have been successfully achieved [30]. Using -potential and quartz crystal microbalance measurements, Brewer et al showed that the conjugation of BSA with gold nanoparticles occurred mostly by an electrostatic mechanism [31].…”
Section: Introductionmentioning
confidence: 99%